Contingent Equity and the Dilutive Effect on EPS. - Barlev, Benzion (The Accounting Review, 1983)
This paper analyzes the modified treasury stocks (MTS) method mandated by APB Opinion No. 15 for computing diluted Earnings Per Share (EPS) figures in cases where warrants are outstanding. It is shown that the MTS method suffers from two basic deficiencies. First, it assumes that funds obtained from exercising the outstanding warrants are used to reduce debt or to purchase Government securities. This introduces exogenous factors (e.g., interest rate) into the process of computing diluted EPS. Second this method is applicable even in those cases where the exercise price of the warrant exceeds the share price. As a result of these deficiencies, dilutive effects are often reduced and even nullified under certain conditions, Moreover, these effects are subject to managerial discretion and, hence, potential manipulation.